Epidemic of Chikungunya in Southernmost of Thailand in 2010 - พริกชู, ปฐมพร; ธรรมปาโล, สุวิช; วงศ์หิรัญรัชต์, วิรัช; แก้วขาว, เรวดี; บัวยอม, ปัจฉิมา; กิมาคม, แจ่มจันทร์ (Disease Control Journal, 2011)
This study was a retrospective descriptive study aimed to study the epidemiology of chikungunya, disease prevention behavior, biology of Aedes albopictus, and environmental factors related to its feeding behavior. Three data sets such as, infectious epidemiological surveillance data, behavioral survey data, and mosquito biting and landing survey between 2009 and 2010 were collected. Results showed that first chikungunya case was reported in February 2009. Cases were increased in May 2009 and the highest cases in June 2009 that were 1,161 and 1,323 cases (morbidity rate 231.03 and 261.91 pop/100,000), respectively. Almost (63.00%) were female and (50.95 %) were agricultural career. Skin lotion or wearing shirt were used (68.95%) to prevent mosquito during rubber tapping and 54.52% used lotion and fan while resting in house. Aedes albopictus was found all year. Biting rate in-house, outside-house, and in garden were 0.47, 0.95 and 2.93 per man per hour, respectively. In lower south of Thailand, population was high susceptibility of chikungunya or emerging vector born diseases due to no firmed prevention in placed so that epidemic may occur if infected patients migrate.